(untitled) (Scientific journal of the Fergana State University, 2025)
This article discusses the interpretation of the image of mother and child in the story "On a Hot Day" by the Turkish writer Yasar Kemal. The tense psychological situation in the story also sheds light on the folklore traditions characteristic of the writer’s style. There is also a reaction to the fact that the unhappy childhood of the writer’s artistic search was transferred to his works as an image.